2012
DOI: 10.1007/s00345-012-0859-4
|View full text |Cite
|
Sign up to set email alerts
|

Penile prosthesis implantation for the treatment for male erectile dysfunction: clinical outcomes and lessons learnt after 955 procedures

Abstract: Penile prosthesis surgery is a safe and durable treatment option for male ED. Strict adherence to antimicrobial prophylaxis and surgical practice is paramount to ensure low complication rates and high patient satisfaction rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 21 publications
2
26
0
1
Order By: Relevance
“…Mechanical reliability of penile prosthesis has increased over time. As stated in previous reports, mechanical failure is more common with former prostheses, which was found to be independent from the etiology as in our study [11,12,14].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mechanical reliability of penile prosthesis has increased over time. As stated in previous reports, mechanical failure is more common with former prostheses, which was found to be independent from the etiology as in our study [11,12,14].…”
Section: Discussionsupporting
confidence: 87%
“…Penile prostheses are subject to continuous development and have gained better mechanical reliability and safety in recent decades [10], but device‐related complications together with the well‐known complications of PPI can still occur [11,12]. With the evolvement of inflatable penile prostheses with infection‐retardant coating, the infection rates have decreased over time.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al . [18] recently published data on penile prosthesis implantation. Most of the 955 men studied were satisfied with the surgical outcomes, and 90% of the men stated that they would undergo prosthesis implantation again.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with decreased satisfaction with penile prosthesis [67]. Long-term follow-up studies showed that at 5 years 1:10 penile prosthesis has to be replaced [69]. Long-term follow-up studies showed that at 5 years 1:10 penile prosthesis has to be replaced [69].…”
Section: Penile Prosthesismentioning
confidence: 99%